2001
DOI: 10.1161/circ.104.suppl_1.i-68
|View full text |Cite
|
Sign up to set email alerts
|

Does Coronary Artery Bypass Grafting Alone Correct Moderate Ischemic Mitral Regurgitation?

Abstract: Background The optimal management of moderate (3+ on a scale of 0 to 4+) ischemic mitral regurgitation (MR) remains controversial. Some advocate CABG alone, whereas others favor concomitant mitral annuloplasty. To clarify the optimal management of these patients, we evaluated the early impact of isolated CABG on moderate ischemic MR. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Surgical correction, either by replacement or repair, is generally recommended for 3ϩ and 4ϩ IMR. [9][10][11] In comparative analyses, repair seems to benefit most patients with IMR, with the possible exception of high-risk groups (higher New York Heart Association [NYHA] functional class or emergency operation). 1,12 In patients who undergo repair, residual MR greater than 1ϩ is associated with increased late mortality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical correction, either by replacement or repair, is generally recommended for 3ϩ and 4ϩ IMR. [9][10][11] In comparative analyses, repair seems to benefit most patients with IMR, with the possible exception of high-risk groups (higher New York Heart Association [NYHA] functional class or emergency operation). 1,12 In patients who undergo repair, residual MR greater than 1ϩ is associated with increased late mortality.…”
Section: Resultsmentioning
confidence: 99%
“…1,[5][6][7][8] Operative mortality is increased for patients undergoing mitral valve operation and revascularization in the presence of IMR when compared with nonischemic MR 4,6,7 or revascularization alone.Surgical correction, either by replacement or repair, is generally recommended for 3ϩ and 4ϩ IMR. [9][10][11] In comparative analyses, repair seems to benefit most patients with IMR, with the possible exception of high-risk groups (higher New York Heart Association [NYHA] functional class or emergency operation). 1,12 In patients who undergo repair, residual MR greater than 1ϩ is associated with increased late mortality.…”
mentioning
confidence: 99%
“…These patients also showed a higher prevalence of cardiovascular mortality, severe heart failure, and recurrent myocardial infarction. Grigioni and colleagues showed that in the chronic phase of a myocardial infarction, the presence of IMR was associated with excess mortality independently of baseline characteristics and severe ventricular dysfunction [4]. Risk of death was directly related to the importance of IMR [4].…”
Section: Discussionmentioning
confidence: 99%
“…Grigioni and colleagues showed that in the chronic phase of a myocardial infarction, the presence of IMR was associated with excess mortality independently of baseline characteristics and severe ventricular dysfunction [4]. Risk of death was directly related to the importance of IMR [4]. In patients undergoing primary percutaneous coronary intervention (PCI) in the set up of an acute MI [16], Pellizzon's study showed that survival was markedly reduced in patients with IMR at both 30 days and 1 year, and increased with severity of mitral regurgitation [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation